TRADISI REJEBAN DI KECAMATAN PAKIS KABUPATEN MAGELANG JAWA TENGAH - Ana Choerunisak (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2020)
The culture that develops in the community is very much influenced by the natural conditions that are inhabited by the community as the producers of culture. This is in accordance with environmental and cultural ecological theory that cannot be seen separately, but is a mixed product that processes through dialectics. presentation of cultural values ​​to the community in Pogalan Village, Pakis District, Magelang, Central Java District, values ​​that should be passed on to the community among other examples, courage, social and personal interaction, responsibility, self-sacrifice, solidarity, cooperation, cooperation, mutual cooperation, courtesy, independence, simplicity, productivity, efficiency.